Principal leadership and teacher work motivation as predictors of primary school teacher performance - Erni, Yusnizar; Syahril, Syahril; Achyar, Novryanti; Sabandi, Ahmad (Universitas Jambi, Indonesia, 2026)
Both organizational and individual factors influence teacher performance, which is a key factor in improving educational quality. This study examines the contribution of principal leadership and teacher work motivation to teacher performance in primary schools in Kinali District, West Sumatra, Indonesia. Using a quantitative correlational design, data were collected from teachers through validated Likert-scale questionnaires and analyzed using descriptive statistics and multiple linear regression with SPSS. The findings indicate that principal leadership and teacher work motivation are positively and significantly associated with teacher performance, both individually and simultaneously. Teacher motivation showed a stronger contribution than principal leadership in explaining variations in teacher performance. The findings highlight the importance of strengthening instructional leadership and supporting teacher motivation as strategies for improving teacher effectiveness in primary schools.